Finno-Ugric Languages in Russian Education: the changing legal-institutional framework and falling access to native language learning - Zamyatin, Konstantin (Études finno-ougriennes, 2014)
After the collapse of the USSR, not only the former union republics, but also autonomous republics and regions inside post-Soviet Russia adopted extensions of native-language teaching in school as one of the central goals of their national revival and language revival policy. To achieve this goal, regional authorities adopted legislation and created an institutional framework for language education. Depending on the resultant configuration of the legal-institutional framework of language education, the dynamics in implementing the goal of language teaching extension in regions varied. How have different regional configurations of the legal-institutional framework affected language teaching? This study explores the position of Finno-Ugric languages in Russian regional education systems using a legal-institutional approach. The effect of the policy is studied by employing calculation of the dynamics in the relative share of native language learners in school. The empirical study demonstrates that the frameworks of teaching the native languages in Finno-Ugric republics and autonomous districts are comparable, but that access to native language learning was provided to differing degrees. Après l’écroulement de l’URSS, les anciennes républiques de l’Union, mais aussi les républiques autonomes et certaines régions au sein de la Russie post-soviétique étendirent l’enseignement de la langue maternelle dans les écoles et en firent l’un des principaux objectifs de la revitalisation nationale et de la politique de revitalisation des langues. Pour réaliser cet objectif, les autorités régionales adoptèrent des lois et donnèrent à l’enseignement des langues un cadre juridique. Suivant la configuration de ce dernier, la dynamique dans la mise en œuvre de l’enseignement des langues vernaculaires a pu différer selon les régions. Comment les différentes configurations régionales du cadre institutionnel et juridique ont-elles influé sur l’enseignement de la langue? Cet article étudie la position des langues finno-ougriennes dans ...